Early Detection and Treatment Speech Delay Children of Preschool Age (Multi-Site Study of 3 Preschool Institutions in Malang City) - Astuti, Ambar Kusuma; Efendi, Mohammad; Rahman, Diniy Hidayatur; Ediyanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to understand: (1) forms of speech delay (2) internal and external factors that affect speech delay, (3) indicators that affect child development (4) procedures for handling speech delay. In order to be able to reveal the phenomena that occur in the community, researchers used the Multisite Study research design where data collection in this study used descriptive qualitative methods with interview, observation and documentation techniques. The researchers conducted interviews with subject parents/teachers in class. Observations researchers do by observing the subject while in the school environment and also at home. Meanwhile, in order for the findings that the researchers carried out to be declared valid, the validity of the data used (1) observation persistence, (2) triangulation, and (3) reference adequacy.The results of the study show that children who experience speech delay or are late in speaking are more dominant due to wrong parenting and a lack of educational/parenting knowledge for parents starting from pregnancy until the child is born. Excessive giving of gadgets makes children less able to carry out 2-way interactions so that it affects children's language development which causes children's communication and behavior to deviate